Seasonal and interannual variability of geostrophic current’s transport in the South Ocean by hydrological and satellite measurements - Artamonov, Yu. V.; Fedirko, A.V.; Kubryakov, A. A.; Skripaleva, E. A.; Stanichny, S.V. (Ukrainian Antarctic Journal, 2013)
On the basis of climatic array World Ocean Atlas-2009 and sea level anomalies altimetry data for 1993–2010 the seasonal and interannual variability of geostrophic current’s transport in the South Ocean is investigated. The connection of geostrophic transport’s spatial-temporal variability with indexes of atmospheric circulation Southern Oscillation and Antarctic Oscillation is analyzed.